Near Infrared Spectroscopy for Monitoring Flap Viability Following Breast Reconstruction - Whitaker, Iain S.; Pratt, George F.; Rozen, Warren Matthew; Cairns, Scott A.; Barrett, Matthew David; Hiew, Leong Yoon; Cooper, Mark ACS; Leaper, David J. (Journal of Reconstructive Microsurgery, 2012)
Free flap monitoring is essential to the early detection of compromise thereby increasing the chance of successful salvage surgery. Many alternatives to classical clinical monitoring have been proposed. This study seeks to investigate a relatively new monitoring technology: near infrared spectroscopy (NIRS). Patients were recruited prospectively to the study from a single center. During the research period, 10 patients underwent reconstruction with a free deep inferior epigastric perforator flap (DIEP). Measurements of flap perfusion were taken using NIRS in the preoperative and intraoperative phases and postoperatively for 72 hours. NIRS showed characteristic changes in all cases which returned to theater for pedicle compromise. In these cases, NIRS identified pedicle compromise prior to clinical identification. There were no false-positives. NIRS accurately identified all compromised flaps in our study. In most cases, there was an evidence of changes in oxygen saturation on NIRS prior to clinical observation. Further research, ideally double blind randomized control trials with large sample groups would be required to definitively establish NIRS as an ideal flap monitoring modality.
Keywords: free flap; perforator flap; reconstructive surgery; monitoring